Uji Efektivitas Ekstrak Daun Rumput Paitan (Paspalum conjugatum) terhadap Kesembuhan Luka Insisi pada Tikus Putih (Rattus norvegicus) - Porat, Andreas E.; Laut, Meity M.; Ndaong, Nemay A. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Indonesia has the largest biodiversity in the world (Megabiodiversity), including Paitan Grass (Paspalum conjugatum) or what will hereinafter be called P. conjugatum, which is a forage plant for livestock (HPT). In several regions such as the Philippines, Kalimantan, Papua New Guinea and Manggarai, this grass is commonly used as a wound medicine. This study aims to determine the effectiveness of Paitan Grass leaf extract on incisional wounds in white rats. The method used was laboratory experimental, using Paitan Grass (P. conjugatum) which was extracted using a maceration technique with 70% ethanol solvent for 3 days, and applied to white rats (Rattus norvegicus) which had been incised in vivo. This study had 3 groups, namely positive control (povidone iodine 10%), negative control (NaCl 0.9%), and Paitan Grass extract. The parameters for observing incisional wound healing in this research were the length of time, speed of hemostasis, wound color, exudate and crusting, and the length of time for wound healing which was measured for 14 days. Measured using a caliper. The results obtained were analyzed using One Way ANNOVA Tukey HSD advanced test. The results showed that Paitan Grass (P. conjugatum) extract was effective in speed of hemostasis (P>0.05) with positive control, color change in 48 hours, exudate visible in 24 hours, crusting and speed of wound healing (P<0.05 ) with both control groups, but there was no significance (P>0.05) between the positive control and negative control.